The Impact of Group Feedback on Self-Perceptions Following Videotape Exposure in CBT for Social Anxiety Disorder. Issue 3 (May 2023) - Laposa, Judith M.; Rector, Neil A.
Video feedback following social anxiety exposures improves self-perceptions. Clinical studies have not examined whether feedback from group members has incremental benefit beyond that of viewing the tape itself. Sixty-seven individuals with social anxiety disorder completed videotaped exposure during group based cognitive behavior therapy (CBT). After participants viewed their taped exposure, group members and therapists gave feedback. Participants completed ratings of anxiety and performance before and after taping their exposure, after viewing the video themselves, and after receiving group feedback. Appraisal of social concerns were assessed after taping, viewing, and group feedback. There were significant improvements in anxiety, performance, and decreased social concerns across time points. Comparing only the time points of after viewing and after receiving group feedback, the same pattern emerged for anxiety, performance, and appraisal of social concerns, with moderate to large effect sizes. Group feedback led to ratings that exceeded their own initial evaluation of their video. Video feedback in group CBT that also includes feedback from others may improve clinical outcomes.